2015
DOI: 10.1523/jneurosci.5029-13.2015
|View full text |Cite
|
Sign up to set email alerts
|

DBZ Regulates Cortical Cell Positioning and Neurite Development by Sustaining the Anterograde Transport of Lis1 and DISC1 through Control of Ndel1 Dual-Phosphorylation

Abstract: Cell positioning and neuronal network formation are crucial for proper brain function. Disrupted-in-Schizophrenia 1 (DISC1) is anterogradely transported to the neurite tips, together with Lis1, and functions in neurite extension via suppression of GSK3␤ activity. Then, transported Lis1 is retrogradely transported and functions in cell migration. Here, we show that DISC1-binding zinc finger protein (DBZ), together with DISC1, regulates mouse cortical cell positioning and neurite development in vivo. DBZ hindere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In utero electroporation. In utero electroporation was performed on E14.5 embryos from timed-pregnant WT ICR mice (SLC, Shizuoka, Japan) 57 . The pregnant mice were anesthetized by intraperitoneal injections with a solution containing 0.3 mg medetomidine (Domitor, Zenoaq Nippon Zenyaku Kogyo, Fukushima, Japan), 4 mg midazolam (Dormicum, Astellas Pharma Inc., Tokyo, Japan), and 5 mg butorphanol (Bettlefar, MP AGRO Co., Ltd., Hokkaido, Japan) per kg.…”
Section: Controlmentioning
confidence: 99%
“…In utero electroporation. In utero electroporation was performed on E14.5 embryos from timed-pregnant WT ICR mice (SLC, Shizuoka, Japan) 57 . The pregnant mice were anesthetized by intraperitoneal injections with a solution containing 0.3 mg medetomidine (Domitor, Zenoaq Nippon Zenyaku Kogyo, Fukushima, Japan), 4 mg midazolam (Dormicum, Astellas Pharma Inc., Tokyo, Japan), and 5 mg butorphanol (Bettlefar, MP AGRO Co., Ltd., Hokkaido, Japan) per kg.…”
Section: Controlmentioning
confidence: 99%
“…The G‐protein‐independent pathway is primarily involved in neurite outgrowth . DISC1 is transported from neuronal soma to the neurite tips via suppression of GSK3β activity to regulate neurites …”
Section: Antipsychotic Drug‐targeted Receptors Regulate Neurites In Smentioning
confidence: 99%
“…An early study showed that a low dose of D2R agonist stimulated neurite outgrowth . However, when there is hyperdopaminergic D2R activation, D2R and DISC1 form a protein complex, which could limit transportation of DISC1 to neurite tips and decreases GSK3α‐Ser21 phosphorylation and GSK3β‐Ser9 phosphorylation, ultimately reducing microtubule elongation in neurites (Figure A and B) . D2R hyperactivity may be induced by an overstimulation of dopamine since there is increased presynaptic dopamine in the schizophrenia brain.…”
Section: Antipsychotic Drug‐targeted Receptors Regulate Neurites In Smentioning
confidence: 99%
“…Plasmids for EGFP-tubulin (#30487, gift from Tso-Pang Yao), mCherry-tubulin (#26768, gift from Torsten Wittmann), tdTomato-EB3 (#58090, gift from Michael Davidson) and pLifeAct-mTurquoise2 (#36201, gift from Dorus Gadella), were obtained from Addgene. Plasmids for EGFP-EB3, K5H-EGFP and dominant-negative Kif5s were as described previously (Konishi and Setou, 2009;Okamoto et al, 2015). K5H-mCherry was constructed by inserting the K5H sequence into pmCherry-N vector (BD Biosciences, Franklin Lakes, NJ).…”
Section: Transfectionmentioning
confidence: 99%